Validity of the Elementary School Mathematics E-Module on Fractional Material Based on the Realistic Mathematics Education (RME) Approach - Hafizah, Nadra; Ahmad, Syafri; Zainil, Melva; Bentri, Alwen (Mimbar Sekolah Dasar, 2024)
This research is motivated by observations that show the lack of additional teaching materials in schools that facilitate students in communicating mathematical ideas (symbols, pictures, and graphs) as well as concepts related to fractions by presenting the surrounding environment as a source of learning. This study aims to reveal the validity level of mathematics e-modules on fractional material based on the RME approach developed. The type of research used is research and development, and the research model used is the ADDIE model, namely the analysis stage, development stage, implementation stage, and evaluation stage. The validity sheet is the instrument used in this study. Researchers analyzed validation sheets with a scale of 5 (five) to determine the quality of the e-modules developed. The results of material expert validation got a score of 0.9  with a very valid category; media expert validation got a score of 0.89 with a very valid category; and linguist validation got a score of 0.9 with a very valid category. So, the mathematics e-module on fractional material based on the RME approach is valid and feasible to use as a mathematics module, especially fractional material, because it has met the assessment criteria.